(untitled) (Asian Journal of Medical Research and Health Sciences, 2026)
Background: Grade III and IV internal hemorrhoids frequently require surgical management. Milligan–Morgan hemorrhoidectomy (MMH) is the conventional gold-standard procedure, whereas Doppler-guided hemorrhoidal artery ligation with recto-anal repair (HAL-RAR) is a minimally invasive, artery-sparing alternative. This study compared postoperative recovery, complications and recurrence between the two techniques. Methods: In a prospective comparative study conducted over 18 months in the Department of General Surgery, 120 patients with grade III or IV internal hemorrhoids were allocated to Group A, MMH (n = 60), or Group B, HAL-RAR (n = 60). Outcomes assessed included operative time, blood loss, Visual Analog Scale (VAS) pain scores at 6 hours and postoperative days 1, 3, 7, 15 and 30, analgesic requirement, hospital stay, return to normal activity, wound healing, complications, six-month recurrence and patient satisfaction. Continuous variables were compared using the independent-samples t-test and categorical variables using Fisher’s exact test; p < 0.05 was considered significant. Results: Baseline demographic and clinical characteristics were comparable between groups (all p > 0.05). Intraoperative blood loss was lower with HAL-RAR (35.8 ± 9.5 ml versus 42.5 ± 9.6 ml, p < 0.001), while operative time did not differ significantly (39.1 ± 8.3 versus 36.8 ± 7.4 minutes, p = 0.112). VAS pain scores were significantly lower in the HAL-RAR group at every postoperative interval (p < 0.001), and analgesic requirement in the first 24 hours was reduced (1.8 ± 0.6 versus 3.1 ± 0.8 doses, p < 0.001). HAL-RAR was associated with shorter hospital stay (1.6 ± 0.4 versus 2.4 ± 0.5 days, p < 0.001) and earlier return to normal activity (7.2 ± 2.1 versus 13.4 ± 3.2 days, p < 0.001). Complication rates and six-month recurrence were low and statistically similar between groups. Patient satisfaction was significantly higher after HAL-RAR (8.7 ± 0.9 versus 7.9 ± 1.1, p < 0.001). Conclusion: HAL-RAR provides significantly less postoperative pain, faster recovery, shorter hospitalisation and higher patient satisfaction than MMH, with a comparable safety and recurrence profile, and may be considered a preferred option in appropriately selected patients with grade III or IV hemorrhoids.